2022
DOI: 10.1177/01939459221107579
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Programming for Older Adults in Assisted Living: Residents’ Perspectives

Abstract: Decreasing sedentary behavior and increasing light physical activity could promote the maintenance of functional abilities for older adults in assisted living (AL). The purpose of this qualitative study was to gather residents’ recommendations about a proposed self-efficacy enhancing intervention to replace sedentary behavior with light physical activity. We interviewed 20 residents (mean age 83.1; 60% women). Topics included their current activities and thoughts about physical activity. We presented the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…This fear stems from the idea that their bodies may be more vulnerable to strain or injury as they age [50,54]. Studies have shown the impact of these fears on older adults' willingness to participate in SB reduction programs [42,47,48,54,60]. These studies highlight the importance of addressing these concerns and ensuring the safety and appropriateness of program activities for older adults.…”
Section: Barriers and Facilitators To Participating In Sedentary Beha...mentioning
confidence: 99%
See 4 more Smart Citations
“…This fear stems from the idea that their bodies may be more vulnerable to strain or injury as they age [50,54]. Studies have shown the impact of these fears on older adults' willingness to participate in SB reduction programs [42,47,48,54,60]. These studies highlight the importance of addressing these concerns and ensuring the safety and appropriateness of program activities for older adults.…”
Section: Barriers and Facilitators To Participating In Sedentary Beha...mentioning
confidence: 99%
“…Lack of motivation, a strong preference for sedentary activities, and deeply ingrained sedentary habits are also significant barriers for older adults to reduce their SB. Some studies have shown that it is difficult to motivate older adults to change their SB because they enjoy sedentary activities such as reading, watching television, or hobbies that require little physical exertion [42,43,47,48,60]. Therefore, it is important to find alternative, nonsedentary activities that are enjoyable and personally meaningful to older people.…”
Section: Barriers and Facilitators To Participating In Sedentary Beha...mentioning
confidence: 99%
See 3 more Smart Citations